Developing A Model On Executive Function Skills And Understanding Of Physics Concepts To Design A Teaching Guide Of Force Concepts And Measuring Its Effectiveness - Tanimale, Bala Murali (2021)
The Executive Function (EF) is "a set of processes that all have to do with managing oneself and one's resources in order to achieve a goal” (Gioia, Isquith, Guy, & Kenworthy, 2015). EF has three main strands: metacognitive, behaviour regulation, and emotional regulation (Gioia et al., 2015), with a wide range of EF skills that fall under these three strands. There is a lack of instruments to measure the EF of Malaysian students and no model to refer to be integrated into teaching and learning of Force and Motion. EF levels of students differ, and the role of EF in teaching and learning physics concepts in Malaysia is minimal. Multiphase design of mixed-method research employed in this study.